ESTUDO DE CASO - USO DE MÉTRICAS PARA DESENVOLVIMENTO DE SISTEMAS INFORMATIZADOS - Moraes, Nielsen Oliveira de (2005)
The goal of this piece of work is to analyze the most common metrics used for the development and maintenance of information systems, under the viewpoint of a Federal Government Institution IT manager. The increasing speed of information that comes from globalization makes it necessary for the companies to have their own information systems. This encourages the service supplying firms to develop techniques for the increase of productivity. In this developing process it is fundamental to take into account the cost of the whole production, not only the cost of the final product. It is also necessary for the companies to control their developing processes. As to the companies that are contracting the services of supplying firm, there is a great necessity of improving the way the computerization expenses are planned and carried out. It is also necessary to follow-up the developing process and make the necessary corrections. Together with that comes the necessity of being familiar with the service supplying firms and particularly being familiar with the firms that take part in the public bidding, being also in a position to evaluate them, deciding which ones have understood the proposed problem and which ones are able to achieve the aimed product. For that purpose we are presenting the most well-known metrics, making a brief study of each one of them and, at the end, pointing out the advantages and disadvantages of each one. It has been noticed throughout the project that much is said about metrics, but little is actually used, which caused a great difficulty to the research. This leads us to the thought of the reasons why the metrics are not always used, when they seem to bring more clarity to the work